2018
DOI: 10.1101/gad.313783.118
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in microRNA processing genes in Wilms tumors derepress theIGF2regulatorPLAG1

Abstract: Many childhood Wilms tumors are driven by mutations in the microRNA biogenesis machinery, but the mechanism by which these mutations drive tumorigenesis is unknown. Here we show that the transcription factor ) is a microRNA target gene that is overexpressed in Wilms tumors with mutations in microRNA processing genes. Wilms tumors can also overexpress through copy number alterations, and expression correlates with prognosis in Wilms tumors. overexpression accelerates growth of Wilms tumor cells in vitro and ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 58 publications
(75 reference statements)
0
29
0
Order By: Relevance
“…Finally, prolonged nephrogenesis was observed also in mice with overexpression of Lin28, -28b or inactivated Let-7 (Urbach et al, 2014, Yermalovich et al, 2019. Despite their great potential, these models show either direct tumorigenesis or are associated with increased activation of Igf2/H19 locus, which associates with pediatric kidney cancer known as Wilms' tumor (Chen, Stroup et al, 2018, Ogawa, Eccles et al, 1993. As a note, no changes in pSMAD1/5 localization or levels were detected in Gdnf hyper/hyper kidneys, which are tumorfree also in aged heterozygotes animals.…”
Section: Discussionmentioning
confidence: 98%
“…Finally, prolonged nephrogenesis was observed also in mice with overexpression of Lin28, -28b or inactivated Let-7 (Urbach et al, 2014, Yermalovich et al, 2019. Despite their great potential, these models show either direct tumorigenesis or are associated with increased activation of Igf2/H19 locus, which associates with pediatric kidney cancer known as Wilms' tumor (Chen, Stroup et al, 2018, Ogawa, Eccles et al, 1993. As a note, no changes in pSMAD1/5 localization or levels were detected in Gdnf hyper/hyper kidneys, which are tumorfree also in aged heterozygotes animals.…”
Section: Discussionmentioning
confidence: 98%
“…Wilms tumor, resulting from deviant cellular proliferation and differentiation, is currently one of the most concerned tumors in children [1,2]. It is also one of the most common solid pediatric tumors, especially before the age of five years [3].…”
Section: Introductionmentioning
confidence: 99%
“…Work with animal models has provided evidence that increased IGF2 expression is an important contributing factor in both BWS and Wilms tumor (Caspary et al 1999;Hu et al 2011;Huang et al 2016). Two studies, Chen et al (2018) in this issue and Hunter et al (2018) in the previous issue of Genes & Development, highlight the significance of IGF2 up-regulation in the context of Perlman syndrome and Wilms tumor, respectively. Hunter et al (2018) addressed the mechanisms underlying Perlman syndrome, which is an autosomal recessive syndrome arising through mutation of DIS3L2 on chromosome 2q37 (Astuti et al 2012).…”
mentioning
confidence: 95%
“…In another interesting study in this issue of Genes & Development, Chen et al (2018) elucidated a regulatory network by which altered microRNA levels may lead to Wilms tumor. Recent studies have shown that in ∼20% of Wilms tumors, mutations of MIRPGs is observed, resulting in altered microRNA levels.…”
mentioning
confidence: 99%
See 1 more Smart Citation